PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS III SDN 010 PASIR PUTIH KECAMATAN BATANG GANSAL - Marhaliani Marhaliani; Damanhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this to improve the result of learning IPA students class III ( Three ) SDN 010 Pasir Putih Batang Gansal of academic Year 2014/2015 by the implementation cooperative learning model type Group Investigation (GI). The subject of the research is student class III ( Three ) SDN 010 Pasir Putih Batang Gansal totally 30 student, consist of 20 male students, and 10 female student. This research classroom action research by consist of two cycle. In cycle 1 consist of two meeting and one meeting a daily test, in cycle 2 consist of two meeting and one meeting a daily test, the instrument of the research include the learning devices (syllabus, RPP, LKS), Sheet observation teacher activity and student. The benefit of the research for teacher as a motivation for increase ability to choose learning model, for students to adding the interest in learning IPA. And to school increase and correct the learning especially for learning IPA. The formulation of the research “ are the application learning model type Group Investigation can be increase theresult of learning IPAstudents class III ( three ) SDN 010 Pasir Putih Batang Gansal?”. The data collection from understanding student test by cycle test. In basic scor the completeness student score 46,7%, in cycle 1 increase be 73,3%, 86,7% in cycle 2. The average in basic scor 68,2%,in cycle 1 inrease be 9,09%,11,29% in cycle 2,increasingly the result of result of learning from basic scor to cycle one increase be, in addition that obtain increasingly for teachers activity and students also, the percentage teachers activity in cycle one 70,8%, in cycle two increase be 87,5%. So that it can be taken the conclusion of the research that by the implementation type Group Investigation in learning can be increase the result of learning IPA students class III ( Three ) SDN 010 Pasir Putih Batang Gansal.Keyword : Type Group Investigation, The Result Of Learning IPA